Handwriting identification : a direction review - Khaled Mohammed Abdl, author; Siti Zaiton Mohd. Hashim, author; International Conference on Signal & Image Processing Applications (2009: Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL